A geometrically defined stiffness contact for finite element models of wood joints. (15th May 2021) - Iraola, B.; Cabrero, J.M.; Basterrechea-Arévalo, M.; Gracia, J.
Highlights: FEA tend to overestimate the elastic response of structural timber connections. The stiffness contact defines the pressure-overclosure relationship of contact areas The proposed stiffness contact improves the joint behaviour obtained by FEM. The stiffness contact parameter is defined only based on geometrical parameters Larger contact areas have a lower value of stiffness contact Abstract: Finite element models tend to overestimate the actual elastic response of structural timber connections. The paper shows how such overprediction relates to the modelling of the contact between fasteners and timber. The use of a control parameter called stiffness contact is proposed. After an experimental campaign, a method to determine it, based only on the geometry of a rectangular contact area, is proposed. The modeling adequacy is demonstrated by applying it to dowel embedment and moment resistant wood joint tests. The obtained results show good agreement with the experimental test series.